A Study on the Role of Advertisements in Instigating Pester Power in Children - TN, Kamala (Ushus Journal of Business Management, 2021)
The advertisements have a direct bearing on the socio-cultural,"m::*:li: academic, and psychological framework of the children. Constant watching of 1V programs and commercials affect child's social behavior. Behavior is referred to the way the child conducts oneself in his/ her social surroundings. Behavioral impact affects not only the child but also the associates and the environment of child's life, mainly comprising of the family, the school and the neighborhood friend, in terms of the shocks experienced by them. The study delves into identifying the impact of advertising on the social setup of child's world. The best way to understand the child's behavior is to look into the child's family and the social circle it is associated with The parent's responses and their opinions, give a true representation of the child's actual behavior. Hence the parents of the respondent children form a focal point of this study